2011
DOI: 10.1111/j.2042-7158.2011.01399.x
|View full text |Cite
|
Sign up to set email alerts
|

Mucus thickness in the gastrointestinal tract of laboratory animals

Abstract: Inter-species variability in mucus thickness along the gut was demonstrated and suggests that the pig resembles more closely the mucus pattern of humans. This may be highly relevant when preclinical animal models are used in drug absorption studies or in the development of oral mucoadhesive drug delivery systems.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
43
0

Year Published

2013
2013
2019
2019

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 61 publications
(48 citation statements)
references
References 68 publications
5
43
0
Order By: Relevance
“…Measurements of mucus thickness in cryostat sections of various laboratory animal species (rat, rabbit, pig) identified a greater thickness in the fundus region of the stomach in the pig (191-222 µm) than in the rabbit (155-277 µm) and in the rat (31-69 µm) (Varum et al 2012). Along the small intestine, mucus was thicker in the rabbit (73-148 µm), followed by the pig (25-54 µm) and the rat (31-34 µm).…”
Section: Oral Routementioning
confidence: 99%
“…Measurements of mucus thickness in cryostat sections of various laboratory animal species (rat, rabbit, pig) identified a greater thickness in the fundus region of the stomach in the pig (191-222 µm) than in the rabbit (155-277 µm) and in the rat (31-69 µm) (Varum et al 2012). Along the small intestine, mucus was thicker in the rabbit (73-148 µm), followed by the pig (25-54 µm) and the rat (31-34 µm).…”
Section: Oral Routementioning
confidence: 99%
“…Mucus is often referred to as a single layer, but it is important to emphasize that studies have identified two layers, namely (i) a firmly adherent mucus layer in connection with the glycocalyx of the epithelial cells and (ii) an overlying loosely adherent layer of mucus [24,25]. As there is discrepancy as to whether the mucus in the small intestine is composed of one or two layers [7,24], the practice of referring to mucus as a single layer is followed in this paper unless stated otherwise.…”
Section: Mucus Function and Compositionmentioning
confidence: 99%
“…In the rat, the total mucus thickness in the gastrointestinal tract was found to range from 120 to 830 lm [24]. Generally, the thickness has been found to be greater in the stomach than in the large intestine, and the small intestine is the gastrointestinal segment with the thinnest mucus lining [24][25][26]. The thickness of the adherent mucus layer is, in contrast to the thickness of the loosely adherent layer, assumed to be independent of hydration and luminal activity [9].…”
Section: Mucus Function and Compositionmentioning
confidence: 99%
See 1 more Smart Citation
“…Since pigs also have an omnivorous diet, their GI tract is very much comparable to that of humans [6,[28][29][30][31]. Since porcine tissue is generally more easily available than healthy human intestinal tissue it allows a more systematic approach to investigate (regional) intestinal absorption of NPs from a biorelevant matrix.…”
Section: Introductionmentioning
confidence: 99%